MENGELOLA UANG RAKYAT DENGAN AMANAH: EVALUASI EFEKTIVITAS BELANJA DAERAH DI PEMERINTAH PROVINSI XX - Dwi Ramadani, Mutiara; Ayu Utami, Widya; Amelia, Firly; Maulidiyah Lubis, Fitrah; Nasirwan, Nasirwan (Jurnal Akuntansi AKTIVA, 2025)
Effective regional financial management based on trustworthy values is an important challenge in realizing a government that truly serves the people. Although regional spending continues to increase every year, its impact on public welfare is not always in accordance with the amount of budget spent. This study examines the effectiveness of regional spending in the Government of Province XX using a descriptive quantitative approach, analyzed through budget effectiveness ratios, development trends reflected in the Human Development Index, Poverty Rate, and Unemployment Rate as well as the application of Islamic principles in the form of trustworthy values in fiscal governance. The results of the study indicate that budget effectiveness is generally high, but has experienced a downward trend from year to year. Regional development indicators show a direction of improvement, and in 2023 there will be a significant increase in the application of trustworthy values, especially in pro-people spending allocations. This finding confirms that the combination of technical efficiency and moral integrity in fiscal policy can strengthen accountability and accelerate the achievement of equitable development goals.